PENYULUHAN KESEHATAN DALAM GIZI SEIMBANG UNTUK ANAK USIA DINI - Saefullah, Encep; Wahdaliansyah, Alhane; Muawanah, Siti; Nur’anah, Nur’anah; Puspaningrum, Choirunisa Diah; Daenuri, Ahmad; Septiani, Dewi Syifa (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Until adolescence, your little one will continue to experience the process of growth and development. At school children aged 6-12 years, children's growth and development does not progress as quickly as when they were toddlers, but is more stable. Therefore, it is important to meet the nutritional needs of school children by providing food with balanced nutritional content in accordance with the needs that refer to the General Guidelines for Balanced Nutrition so that their growth and development occurs optimally. This service activity aims to provide education to the community, especially early childhood or school age children in the form of health education. As a result of implementing this activity, young children's knowledge and understanding of health, especially regarding nutrition, has increased